TI_GERICHTE 52.2006.19 vom 10. März 2006 , Licenza per la creazione di un ristorante in zona mista residenziale artigianale - TI Tribunale d'appello (2006)
Licenza per la creazione di un ristorante in zona mista residenziale artigianale